Zgodbe Prešernovih rokopisov - Hladnik, Miran (Slavistična revija, 2016)
France Prešeren's manuscripts have been of interest to literary historians, collectors, and Slovene general public. The paper summarizes the history of their findings and relocations, thus drawing upon earlier Prešeren scholarship and documenting some previously lesser- and unknown participants in manuscript circulation.
Keywords: autograph; avtograf; collector; falsification; falsifikat; literarno posredništvo; literary mediation; manuscritps; Prešeren, France, 1800-1849; Prešernology; prešernoslovje; rokopisi; Slovene literature; Slovene poetry; Slovene poets; slovenska književost; slovenska poezija; slovenski pesniki; zbiratelji